PENGEMBANGAN KAWASAN STRATEGIS MINAPOLITAN MELALUI KLASIFIKASI WILAYAH DI KABUPATEN KUTAI KARTANEGARA - Adiwibowo, Candra Rizki (SPECTA Journal of Technology, 2020)
Kutai Kartanegara Regency has 7 subdistricts which are included in the Minapolitan area, including Marang Kayu, Muara Badak, Loa Kulu, Loa Janan, Samboja, Muara Jawa and Anggana. In developing the Minapolitan Straegis Region, it can increase fish farming income so as to produce equality in each region with better quality of life and welfare. In carrying out the development, it is necessary to have a region or sub-district which is the center of Minsan Metropolitan services, in determining the Minapolitan Region Service Center in Kutai Kartanegara Regency, a scalogram analysis (Guttman Scale) is performed to determine the areas that have complete facilities related to Minapolitan and Marshall Central Index Index analysis ( ISM) to determine the service center of the Kutai Kartanegara District Minapolitan Area. Based on the two analyzes, a service center in the Kutai Kartanegara District was obtained, namely Anggana District with the type and number of complete facilities related to the Minapolitan Area. Based on these results it is possible to develop the area in Anggana Subdistrict which is the Minapolitan Area Service Center of Kutai Kartanegara Regency. Keywords: Marshall Central Index Index (ISM), Minapolitan Area Service Center ,Scalogram Analysis (Guttman Scale).